Turbulent Fluid Flow - Bernard, Peter S. (John Wiley & Sons, Incorporated, 2018)
A guide to the essential information needed to model and compute turbulent flows and interpret experiments and numerical simulations Turbulent Fluid Flow offers an authoritative resource to the theories and models encountered in the field of turbulent flow. In this book, the author - a noted expert on the subject - creates a complete picture of the essential information needed for engineers and scientists to carry out turbulent flow studies. This important guide puts the focus on the essential aspects of the subject - including modeling, simulation and the interpretation of experimental data - that fit into the basic needs of engineers that work with turbulent flows in technological design and innovation. Turbulent Fluid Flow offers the basic information that underpins the most recent models and techniques that are currently used to solve turbulent flow challenges. The book provides careful explanations, many supporting figures and detailed mathematical calculations that enable the reader to derive a clear understanding of turbulent fluid flow. This vital resource: - Offers a clear explanation to the models and techniques currently used to solve turbulent flow problems - Provides an up-to-date account of recent experimental and numerical studies probing the physics of canonical turbulent flows - Gives a self-contained treatment of the essential topics in the field of turbulence - Puts the focus on the connection between the subject matter and the goals of fluids engineering - Comes with a detailed syllabus and a solutions manual containing MATLAB codes, available on a password-protected companion website Written for fluids engineers, physicists, applied mathematicians and graduate students in mechanical, aerospace and civil engineering, Turbulent Fluid Flow contains an authoritative resource to the information needed to interpret experiments and carry out turbulent flow studies.